COVID-19 pandemic and alcohol consumption: Impacts and interconnections. (2021) - Calina, Daniela; Hartung, Thomas; Mardare, Ileana; Mitroi, Mihaela; Poulas, Konstantinos; Tsatsakis, Aristidis; Rogoveanu, Ion; Docea, Anca Oana
Graphical abstract: Highlights: During lockdown of COVID-19 pandemic alcohol consumption patterns changed. Increased alcohol consumption is associated with many physical ailments and mental disorders. WHO discourages the use of potentially addictive substances to manage the burden of social isolation. Medium and long-term consequences should be investigated in-depth and addressed. Abstract: Alcohol consumption is associated with multiple diseases and might contribute to vulnerability to SARS-CoV-2 infection. It can also catalyze exacerbations of mental and organic illnesses and predispose to behaviors with an increased risk of infection, severity of disease but also independently of sociopathic behavior and violence. Globally, millions of premature deaths from excessive alcohol consumption occur each year. This paper discusses the effects of increased alcohol consumption and the most important consequences on the health of the population during the social isolation and lockdown during current COVID-19 pandemic.